Para a crítica ontológica ao Direito: a gênese do complexo jurídico no Lukács tardio - Ferreira, Júlio Ivo Celestino (2018)
This present work has as its main objective to present the conception of the origins of Law from the Hungarian philosopher’s late work, György Lukács. Accordingly, its core pervades one of the key foundations of the materialism dialectic, which is the relationship between the concrete totality and its constitutive segments. Therefore, by exposing the origins the juridical organization, we aim to contribute to the apprehension of the development and the social function of Law within social totality as well as its reflection and heterogeneity relations to other social complexitites, specially politics, economy, morality, and ethics. To this purpose, we carried out an immanent analysis of the second volume of the Ontology of Social Being, Lukács’ last work. The dialogue with the Lukascian texts will be mediated by the very Hungarian philosoper’s interlocutions: on the one hand with Marx’s, Engels’, and Lenin’s works and a large section of the marxist tradition; on the other hand with authors connected to different traditions of thought such as Aristotle, Nicolai Hartman, Gordon Childe, Werner Jaeger, etc. On top of that, we made use of contributions by the main Brazilian and foreign commentators of the Lukascian work, like István Mészáros, Nicolas Tertulian, Carlos Nelson Coutinho, José Paulo Netto, Leandro Konder, Sérgio Lessa, Ester Vaisman, Vítor Sartori, etc. Thus, alike Lukács, this work proposes to refute not only the idealistic conceptions on the juridical phenomenon but also those derived from a vulgar materialism. To the extent that it rejects, on the one hand, that the law is the fruit of an ahistorical transcendence, on the other that it is mechanically determined by the economy. Having said that, the Lukáscian tertium datur qualifies itself as an ontological criticism to Law, testifying its genesis associated to the immanent development of the social totality and the complexification of the division of labor, which creates the need for a new particular social complex, the juridical complex, to attend to new functions generated within the division of society into social classes. Then, at the same time, the Lukacsian critique also reveals the presuppositions for overcoming the "narrow legal right" with the dissolution of class society itself, and with it, the suppression of the need for any kind of juridical regulation.